Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Think Talk Write Pada Kelas IV SD - Sitanggang, Anggi Pratiwi Putri; Fachrudin, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This purpose of this research is to describe the Improvement of Learning Outcomes of Students Using Cooperative Think Talk Write (TTW) Type in Class IV Elementary Integrated Thematic Learning. The type of research is PTK with qualitative and quantitative. The research subjects were teachers and 22 students of grade IV. The results showed that: (1) the average RPP ranking of cycle I was 84.72% to 92% in the second cycle with an increase of 7.3%, (2) the results of monitoring the activities of teacher cycles I 80.4% to 92.9% in the second cycle with a 12% increase and the results of observations of the activities of students in the first cycle 80.4% to 92.9% in the second cycle with an increase of 12%, (3), and the results of the knowledge aspect of the first cycle 2.66 to 3.66 in cycle II with an increase of 1% and the results of the skills aspect of cycle I 3.00 to 4.00 in the second cycle with an increase of 1%.